The History of Protected Areas in Colombia, their Forms of Government and Governance Alternatives - Rojas Lenis, Yazmín (Sociedad y Economía, 2014)
The paper shows how the strategy for protected areas in the country emerges from thedeveloping models projected from late thirty’s and how the National System of ProtectedAreas (SINAP) a process built through subjective modeling structures crisis adjustmentsand restructuration, according to Sanda Kaufman’s perspective on socio-ecological systems.For its development, the case study method was used with literature review ofaggregate data. This article concludes with reflections on progress and risks facing thisunstable system that must succeed in producing answers or effective adaptations tochanges by using its anticipation and learning capacities. To make their learning capabilitiesadvance and allow you to build effective responses or effective adaptations tochange.